Intergovernmental Fiscal Transfer in Nepal: Does It Lead to Greater Accountability at the Local Level? - Acharya, Keshav Kumar; Bhusal, Thaneshwar (Public Governance, Administration and Finances Law Review, 2024)
The Intergovernmental Fiscal Transfer (IGFT) is a crucial tool for local governments (LGs) to bridge fiscal disparities by providing the necessary funds to fulfil their functional responsibilities. In the context of federal Nepal, IGFT has been classified into four types: fiscal equalisation, conditional, special and matching grants. This research is an attempt to examine the effectiveness of these transfer types in enhancing the local governments’ accountability in Nepal. Through a combination of quantitative and qualitative data types, this study collected primary and secondary data from seven purposively selected municipalities. Our analysis finds that IGFT serves as a powerful tool for advancing accountability among local governments in Nepal. However, the current trend of centralisation within federal government agencies, limited bureaucratic capabilities at both federal and local levels and inadequate political commitment to IGFT have hindered accountability at the local level.